Lightweight, surface hydrophobic and flame-retardant polydimethylsiloxane foam composites coated with graphene oxide via interface engineering - Shen, Fei-Xiang; Li, Yang; Chen, Zuan-Yu; Cao, Cheng-Fei; Shen, Yan-Bin; Li, Long-Tao; Pan, Long-Qian; Li, Jia-Yun; Zhang, Guo-Dong; Gao, JieFeng; Shi, Yongqian; Song, Pingan; et al. (Progress in organic coatings, 2024)
Silicone rubber foam (SiRF) is increasingly recognized as a versatile polymeric foam in industrial applications, owing to its broad temperature stability, weather resistance, and outstanding thermal insulation properties. However, the inherent flammability of SiRFs limits their application in certain areas. Previous attempts to enhance the flame retardancy of SiRFs typically involved the addition of various functional fillers and complex assembly strategies, which often lead to complicated processes, weak interfacial bonding, and potential degradation of other key properties. Therefore, preparing flame-retardant silicone rubber using a simple, low-filler, and large-scale production strategy is a significant challenge. In this study, we introduce a self-adhesive silicone rubber foam (Sa-SiRF) modified with residual Si-H reactive groups using a straightforward dip-coating method, employing graphene oxide nanosheets (GO) for this enhancement. The refined Sa-SiRF-GO nanocomposite exhibits exceptional mechanical properties across a temperature range of 30–200 °C, as well as remarkable surface hydrophobicity, evidenced by a high water contact angle (WCA) of approximately 142.6°. Additionally, this material demonstrates robust structural stability under varying environmental conditions (pH = 1, 7, 14), and an improved flame retardancy, with the limiting oxygen index (LOI) rising from 21.5 % to 27.0 %. Furthermore, a comprehensive analysis of the flame retardation mechanism of Sa-SiRF-GO samples was conducted. This flame-retardant silicone rubber foam, developed through a GO-enhanced dip-coating process, shows great promise for applications that require both flame retardancy and thermal insulation. Our approach, which leverages interfacial engineering to create GO-coated self-adhesive SiRF composites, effectively overcomes the limitations associated with high filler content and the complexities of traditional methods. This innovative technique is poised to spur further advancements in conventional PDMS foams and contribute to the development of advanced polymer foam nanocomposites. [Display omitted] •A multifunctional composite material was designed and fabricated by coating GO solution onto the surface of SiRF with residual Si-H bonds at room temperature.•The residual Si-H bonds on SiRF reacted with GO and enabled firm attachment of GO onto the SiRF surface.•Surface modification of SiRF was achieved by assembling an ultra-low content of GO onto the surface.•The optimized GO-Sa-SiRF exhibited excellent flame retardancy, hydrophobicity and stable mechanical performance.